Toward new dominations: Flawed devotions to human rights discourse and its contingent hope - Abdelkarim, Shaimaa Ragab Hassan (AUC Knowledge Fountain, 2016)
Human rights movement dominates over how people articulate their interests to be heard. It controls massive resources in the name of those interests. This dissertation articulates a path for new emancipation projects to hinder the domination of the human rights movement. Devotion to the movement maintains the illusion of objectifying people’s interests outside politics. Though, the movement fails to deliver on that objectification when activists choose between competing interests, deferring their failures to the future. That temporal space holds the movement’s universal claim. The instability of the movement lies in the gap between what it promises and what it delivers, creating its emancipatory and imperial sides. I argue that the present gets filled up with development towards economic growth, which justifies the universal claims of the movement while the movement justifies the absence of development. The movement acquires the role of representing the universal function with the aid of development. Power holds that representation, which becomes contingent. The contingency of the representation of the universal function is hopeful for different emancipation movements to compete along the human rights discourse. I retain the universal as an empty ground to disprove the fullness of the universal function. Then, I move to suggest that the Other, with the plurality inside that category, can either struggle for the representation for the universal function or for utilizing the emancipatory side of the rights discourse. I choose the former. I urge new liberation projects to fight for the representation of the universal function, without essentializing the subaltern voices, since all Other(s) can struggle their way(s) towards new forms of dominations. Essentializing the subaltern voices within the plurality gains them recognition within the hegemonic. But, I fight for the liberation in struggling rather than recognition; for the Other(s)’ laments to dominate over the rights’ laments.